KUALITAS PRODUK DAN HARGA DALAM MEMODERASI KUALITAS PENGALAMAN TERHADAP NIAT BELI ULANG KEMBALI (REVISIT) (Studi Pada Produk Shampo Pantene) - Ergo Nurpatria Kurniawan; Adam Ariansyah Pirdaus; Chairunnisa Saliasna; Firnanda Eka Wardani; Surya Bintarti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Based on existing data, hair damage experienced by a number of Indonesian people has resulted in a large number of hair washing soaps appearing. Pantene shampoo was owned by a Swiss drug company, Hoffman-LaRoche, until 1985, after which a multinational company from the United States, Procter & Gamble, acquired and started producing Pantene shampoo again. which is one of the pioneers of hair washing soap took first place in the Top Brand Awards, the circulation of hair washing soap from many other manufacturers has influenced the ranking and sales of Pantene shampoo, although it has been involved in hair washing soap products for a long time. The purpose of this study was to examine the effect of experience quality on repurchase intention with product quality and price as moderators. The research was conducted within the boundaries of the community area of ​​West Java province. The number of samples obtained was 108 respondents. This research shows that the quality of experience has an effect on repurchase intention, the quality of experience moderated by product quality has no effect on repurchase intention, while the quality of experience which is moderated by price has no effect on purchase intention.